2012
DOI: 10.1007/s10886-011-0056-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Signals of Elephant Musth: Temporal Aspects of Microbially-Mediated Modifications

Abstract: Mature male African (Loxodonta africana) and Asian (Elephas maximus) elephants exhibit periodic episodes of musth, a state in which serum androgens are elevated, food intake typically decreases, aggressiveness often increases, and breeding success is enhanced. Urine is a common source of chemical signals in a variety of mammals. Elephants in musth dribble urine almost continuously for lengthy periods, suggesting that the chemicals in their urine may reveal their physiological condition to conspecifics. We inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 36 publications
0
20
1
Order By: Relevance
“…Perhaps synergism also derives from the additional modification of compounds in mixed signals. With growing appreciation for the role of bacterial fermentation in odorant production [ 34 , 66 ] and decay [ 39 ], we now recognize that unique communities of obligate or facultative anaerobic microbes inhabit warm, moist scent glands and produce many of the chemical compounds (e.g. volatile fatty acids: [ 67 ]) used by their hosts in olfactory signalling [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps synergism also derives from the additional modification of compounds in mixed signals. With growing appreciation for the role of bacterial fermentation in odorant production [ 34 , 66 ] and decay [ 39 ], we now recognize that unique communities of obligate or facultative anaerobic microbes inhabit warm, moist scent glands and produce many of the chemical compounds (e.g. volatile fatty acids: [ 67 ]) used by their hosts in olfactory signalling [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting composite mark includes a long-lasting white paste and a more ephemeral brown paste that, in addition to their visible contrast, differ in their chemical composition [ 37 ]. The chemical compounds within any given scent signal routinely range in structure, volatility and longevity [ 34 , 35 , 38 , 39 ]. Information can be conveyed by single compounds [ 33 ] or classes of compounds [ 40 ], by their presence or absence, relative ratios, absolute abundances [ 41 ] or by the entire odour mosaic [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…A series of alkan-2-ones and alkan-2-ols were identified in the urine of African elephants using GC-MS [146]. It was suggested that after performing analysis that GC-MS could serve as ‘time-release chemical signals’ to conspecifics [36,149]. …”
Section: Resultsmentioning
confidence: 99%
“…Similar patterns are evident among mammals that communicate via urine marking as well. For example, microbes associated with the urine marks of male African elephants, Loxodonta africana, are responsible for the production of urinary ketones and alcohols believed to signal male musth status [52,53]. Similarly, microbes in the urine marks of house mice (Mus musculus) appear to function in communicating individualand genotype-specific information among competitors and prospective mates [54,55].…”
Section: Chemosensory Detection Of Microbial Productsmentioning
confidence: 99%